The efficacy and safety of first-line anti-seizure medications as substitution therapy for children with drug-resistant epilepsy: a randomized controlled trial protocol - Perdani, Roro Rukmi Windi; Arozal, Wawaimuli; Mangunatmadja, Irawan; Kaswandani, Nastiti; Handryastuti, Setyo; Medise, Bernie Endyarni; Hardi, Harri; Thandavarayan, Rajarajan Amirthalingam; Oswari, Hanifah (Frontiers in Neurology, 2023)
Although many anti-seizure medications (ASMs) are available, treatment failure, known as drugresistant epilepsy (DRE), still occurs in around 30% of children with epilepsy. Second-line ASMs are usually used as substitution therapy in DRE to control seizures, although international consensus is not available yet. Previous studies focus on comparing the ASMs, whether as add-on or substitution therapy, mainly conducted in newly diagnosed epilepsy. However, the study that investigated firstline ASMs as substitution therapy compared to second-line ones, particularly among DRE children, is still lacking. A randomized controlled trial (RCT) enrolling 102 participants, aged 1-18, at three referral hospitals in Indonesia will be conducted, dividing them into intervention and control groups. The intervention group will be treated with first-line ASMs as the substitution therapy, while the other in the control group will get second-line ASMs. The primary outcome measure is the proportion difference of responders between groups who get first-line and second-line ASMs in 14 weeks of intervention.